Tumoral Melanosis in the Setting of Targeted Immunotherapy for Metastatic Melanoma—A Single Institutional Experience and Literature Review. (January 2021) - Jurgens, Andrea; Guru, Swadha; Guo, Ruifeng; Brewer, Jerry; Bridges, Alina; Jakub, James; Comfere, Nneka
Abstract : Background: Tumoral melanosis clinically resembles metastatic melanoma, occurs in the context of regressed disease, and requires evaluation to rule out underlying melanoma and metastatic disease. Histopathology demonstrates a nodular infiltrate of melanophages in the dermis, subcutaneous tissue, deep soft tissue, or lymph nodes in the absence of viable melanocytes. Recent limited reports of tumoral melanosis in the context of immunotherapy with ipilimumab (monoclonal antibody targeting CTLA-4) as well as nivolumab and pembrolizumab (humanized monoclonal antibodies against programmed death 1 receptor) highlight a unique presentation representative of treatment-related tumor regression and an association with a favorable clinical response. Objective: To describe our experience with tumoral melanosis in the setting of immunotherapy for metastatic melanoma and elucidate the clinical and histopathological features. Methods: Retrospective case series from a single tertiary care institution. Results: We describe 10 cases of patients with metastatic melanoma who received treatment with immunotherapy before the development of tumoral melanosis. Length of time between the initiation of therapy and the onset of tumoral melanosis ranged from 2 to 20 months with a mean time of 10 months. At the end of the follow-up period, 8 patients were classified as having a complete or partial response to treatment with immunotherapy. One patient had progression of visceral and cutaneous disease on ipilimumab despite developing tumoral melanosis, and 1 patient had yet to undergo repeat imaging. Furthermore, at the end of follow-up, 3 patients were alive with no evidence of active disease, 5 patients were alive with disease, and 1 patient was deceased, although this patient died of a cardiovascular event unrelated to his underlying melanoma. Of the patients who were classified as alive with disease, 2 patients had minimal remaining disease, and 2 patients had an almost complete response on immunotherapy with recurrence of visceral metastases after immunotherapy was discontinued. One patient developed new peritoneal and cutaneous metastases on pembrolizumab despite development of tumoral melanosis. Conclusions: The underlying biologic mechanisms and prognostic implications of tumoral melanosis in the setting of immunotherapy remain to be elucidated. Further prospective studies with a larger cohort and prolonged follow-up are necessary to better understand the incidence, prevalence, and oncologic outcomes in patients with tumoral melanosis who receive immunotherapy.